Inventário de Habilidades Sociais para Familiares Cuidadores de Pacientes Psiquiátricos (IHS-FCPP): construção e análises psicométricas preliminares - Lima, Diego Costa (2019)
The families of psychiatric patients, despite being recognized as the main caregivers, do not yet receive the necessary guidance to deal appropriately with their care demands. This situation compromises the treatment and the social reintegration of these patients in the community. Currently, there are tools to evaluate some of these contingencies, but none specifically addressed to investigate social skills (SS) and other skills recognized as crucial to help family caregivers in this task. This study focuses these questions and is structured in two chapters that present the process of developing a rating scale – named as Inventory of Social Skills for Family Caregivers of Psychiatric Patients (IHS-FCPP) - and the preliminary evidences of its psychometric properties. Chapter 1 presents an integrative literature review that showed that family members need a more elaborate SS levels. Concerning interventions, the results showed positive effects. However all instruments used for evaluation were not constructed for contexts and demands of psychiatric patients' caregivers. Considering the situational character of SS and the particular conditions of daily care of psychiatric patients, it was understood as important to produce and validate a specific instrument to evaluate the SS typical of these caregivers' routine. In Chapter 2, the objective was to describe the process and the results of the elaboration of the items and to produce preliminary evidences of validity and reliability of the IHS-FCPP. This chapter was organized in four studies. Study 1 presented the evidences of content validity. The items were elaborated from interviews with family caregivers, professionals from Psychosocial Care Centers and other instruments. Then the validity of content was verified by consulting seven professionals, resulting in a pilot version, tested with a sample of the target population. After the removal of items presenting difficulty of comprehension, a version of 70 items was obtained. Study 2 aimed to analyze evidence of validity based on the internal structure and reliability of the IHS-FCPP. The Exploratory Factor Analysis indicated a structure of three factors, with satisfactory reliability, that were denominated as: F1, SS of Assertiveness and Educational Supervision (HSA&SE); F2, SS of Emotional Support (HSSE); and F3, SS of Affectivity and Empathy (HSAE). Study 3 aimed to verify validity evidences based on the association of HS measurements with external indices of subjective burden and quality of life. The results were consistent with the literature. Study 4 aimed to produce preliminary norms and characterize the SS repertoire in their association with sociodemographic variables. The results showed groups at risk in terms of SS deficits, for example those with lower levels of schooling. As a conclusion for the several studies presented here, preliminary psychometric qualities of the IHS-FCPP are recognized, but also the need for more evidence of validity to recommend its use as a diagnostic tool. It is understood that IHS-FCPP can be used in descriptive research and studies on the effectiveness of interventions aimed at the empowerment of family caregivers of psychiatric patients.